(untitled) (Journal of Economic Research & Business Administration, 2015)
The current system of social assistance to the most needy in Kazakhstan as a result of inefficient and increase the cost of the traditional areas of social policy (especially pensions) ceases to contribute even a statistical improvement in the situation of absolute poverty. The main reason that the increase in spending on social policy does not lead to the balanced reduction of absolute poverty is the allocation of resources on the basis of belonging to a certain category of citizens (support status groups) and not on the basis of means-testing. Regulatory constraints are not currently allow you to quickly implement targeted social assistance, based on means-tested, which would replace the existing categorical exemptions and the classical system of social insurance. In this connection, it is expedient to provide for a phasing implementing targeted social assistance, and proposed that the following stages of implementation of targeted social assistance system based on means-testing. Consider the advantages of the decentralized approach to the introduction of targeted social assistance. Social support is provided to enter into binding social contract providing for the social adaptation of the able-bodied unemployed household members.